A Formate Dehydrogenase Confers Tolerance to Aluminum and Low pH . Issue 1 (28th March 2016) - Lou, He Qiang; Gong, Yu Long; Fan, Wei; Xu, Jia Meng; Liu, Yu; Cao, Meng Jie; Wang, Ming-Hu; Yang, Jian Li; Zheng, Shao Jian
Abstract : A Vigna umbellata formate dehydrogenase, VuFDH, confers tolerance to Al and low pH by regulating formate metabolism in plants. Abstract: Formate dehydrogenase (FDH) is involved in various higher plant abiotic stress responses. Here, we investigated the role of rice bean ( Vigna umbellata ) VuFDH in Al and low pH (H + ) tolerance. Screening of various potential substrates for the VuFDH protein demonstrated that it functions as a formate dehydrogenase. Quantitative reverse transcription-PCR and histochemical analysis showed that the expression of VuFDH is induced in rice bean root tips by Al or H + stresses. Fluorescence microscopic observation of VuFDH - GFP in transgenic Arabidopsis plants indicated that VuFDH is localized in the mitochondria. Accumulation of formate is induced by Al and H + stress in rice bean root tips, and exogenous application of formate increases internal formate content that results in the inhibition of root elongation and induction of VuFDH expression, suggesting that formate accumulation is involved in both H + - and Al-induced root growth inhibition. Over-expression of VuFDH in tobacco ( Nicotiana tabacum ) results in decreased sensitivity to Al and H + stress due to less production of formate in the transgenic tobacco lines under Al and H + stresses. Moreover, NtMATE and NtALS3 expression showed no changes versus wild type in these over-expression lines, suggesting that herein known Al-resistant mechanisms are not involved. Thus, the increased Al tolerance of VuFDH over-expression lines is likely attributable to their decreased Al-induced formate production. Taken together, our findings advance understanding of higher plant Al toxicity mechanisms, and suggest a possible new route toward the improvement of plant performance in acidic soils, where Al toxicity and H + stress coexist.